Development of Constructivism-Based Student Worksheets on Free Radical Reaction Material - Okma Rahmatya; Susilawati Susilawati; Maria Erna (Universitas Riau, 2019)
Organic Chemistry is one of the difficult subjects, especially in reaction and strechochemical mechanisms. One effort to reduce it is to utilize teaching materials. This study aims to develop organic chemistry teaching materials on free radical reaction material in the form of constructivism-based student worksheets (LKM). The research method used research and development research design with a 4D development model which consists of the stages of define, design, development, and disseminate. Development of LKM was assessed based on validity criteria and limited trials. The validity of LKM was achieved and assessed by three validators. Limited trials were conducted for the 6th semester students of the chemical education study program totaling 15 people and also three organic chemistry lecturers to see the appropriateness of developed LKM from the lecturers' perspective. The overall LKM results of its validity showed that the LKM has 95.05% valid. The results of limited trials based on the responses of students and lecturers each obtained a percentage of 84.02% and 87.22%, respectively. Based on the results of validation and limited testing of constructivism-based LKM on the material of free radical reaction developed it is included in the category of valid and can be used in the learning process.